Peran manajemen sumber daya manusia dalam meningkatkan kinerja organisasi - Royyani, Mochammad Imdad (Maliki Interdisciplinary Journal, 2025)
This paper discusses the strategic role of human resource management (HRM) in improving organizational performance amid global challenges and digital transformation. HRM encompasses various aspects, from recruitment, training, and compensation to maintaining a quality workforce. In the context of modern organizations, HRM is not only focused on achieving business objectives but also on the well-being and development of individual potential. This paper analyzes the main functions of HRM, such as staffing, performance appraisal, professional training, and occupational safety, as well as the importance of balanced and long-term oriented human resource planning. Furthermore, this paper highlights the negative impact of low-quality human resources on productivity, innovation, and public services. Using a descriptive-qualitative approach, this paper highlights that effective HRM management is the main foundation for achieving an adaptable, competitive, and sustainable organization. Recommendations focus on the importance of investing in education, training, and leadership to create superior human resources ready to face global challenges.